A study on nonlinear absorption uniformity in a KDP crystal at 532 nm. Issue 32 (30th July 2020) - Xu, Longyun; Lu, Chengwei; Wang, Shenglai; Huang, Pingping; Liu, Hui; Zhang, Liyuan; Li, Xianglin; Wang, Bo; Wang, Duanliang
Abstract : The dependence of nonlinear absorption on different growth regions in KDP crystals was explored in detail by z -scan technique. Abstract : KDP crystals were grown using rapid techniques and conventional temperature cooling methods. The nonlinear absorption of various growth sections in the crystals was explored using the z -scan technique. It was shown that the nonlinear absorption coefficient of the KDP crystals, grown using rapid techniques, is greater than that of conventional crystals. The largest nonlinear absorption response was discovered at the interface between the pyramid and prism sections; however, the nonlinear absorption of the prismatic sector was smaller than that of the pyramidal sector of the crystal. The nonlinear absorption of the crystals decreased with increase in supersaturation. The value of nonlinear absorption became larger when the conventional specimen was closer to the regenerated cap.